(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2018)
Motivating others is truly an art. Through constructive delegation practices, conscientious work monitoring, and the provision of meaningful feedback, we can motivate others to perform to the extent of their ability. These managerial skills will serve as the foundation for excellence in overall associate management, mentoring, and professional development. Well-managed people are motivated to continue developing skills to meet the desired expectations as people are under less stress because they have a motivated, well-trained with workforce in place. This paper is presented to help understand the relationship between motivation and self-regulated learning. Self-regulated learning can be facilitated by the adoption of mastery and relative ability goals and hindered by the adoption of extrinsic goals. Summary analyses provided support for the theory that the pursuit of performance goals has an undermining effect on intrinsic motivation relative to the pursuit of mastery goals. Moderator analyses were conducted in an attempt to explain significant variation in the magnitude and direction of this effect across studies. These findings provide conceptual clarity to the intrinsic and extrinsic motivation and suggest numerous avenues for subsequent pragmatic motivational strategies.